Impact of variable thermal conductivity on couple-stress Casson fluid flow through a microchannel with catalytic cubic reactions - Roja Ajjanna; Khan Umair; Sollapur Shrishail B.; Singh Rahul; Prakash Chander; Elattar Samia (High Temperature Materials and Processes, 2025)
This study analyses the entropy and heat transfer characteristics of couple-stress Casson fluid in a porous vertical microchannel, incorporating the effects of isothermal cubic autocatalytic chemical reactions, variable thermal conductivity, uniform heat source/sink, and thermal radiation. The governing equations are transformed into dimensionless form and solved numerically using the fourth and fifth-order Runge-Kutta-Fehlberg method. Key findings reveal that the inverse couple-stress parameter and variable thermal conductivity, significantly influence temperature distribution and fluid flow, enhancing heat transfer efficiency throughout the microchannel system. The study also highlights that homogeneous-heterogeneous reactions reduce concentration levels, improving lubrication and optimizing thermal performance. Additionally, entropy generation increases with higher Biot number, variable thermal conductivity, radiation, and heat source/sink effects. The Nusselt number decreases with increasing thermal conductivity, while drag force minimizes as the inverse couple-stress parameter rises. These findings contribute to the optimization of microfluidic thermal systems, with practical applications in energy-efficient cooling technologies, microchannel heat exchangers, advanced chemical reactors, and biomedical engineering, where precise heat and mass transfer control is essential for improved performance and efficiency.